Increasing Resistance to Ceftriaxone in Pediatric Intensive Care Units - Chaudhary Ehtsham Azmat Abdul Basit Shah Vardag Ahmed Moosa Kazi Muhammed Ammad- Ud-Din Faraz Iftikhar Hassan Liaqat Nadeem Ikram, Chaudhary Ehtsham Azmat Abdul Basit Shah Vardag Ahmed Moosa Kazi Muhammed Ammad- Ud-Din Faraz Iftikhar Hassan Liaqat Nadeem Ikram (Students’ Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Cephalosporins are one of the most widely and generously used antibiotics in treatment of infections in patients admitted to the hospital. However due to their over use, resistance to 3rd generation cephalosporins like ceftriaxone is becoming increasingly widespread. The aim of the study was the assessment of prevalence of microbial resistance to above mentioned drug in the pediatric intensive care units of Holy Family Hospital and Benazir Bhutto Hospital when used in treatment for bacterial infections. Methods: In this descriptive cross-sectional study, 253 pediatric patients of pediatric intensive care units, data was taken from records of the Pathology Department of Holy Family Hospital and Benzair Bhutto Hospital from the September 2016 to July 2017. Collected data includes the information regarding the culture positive microbes, and the antibiotic sensitivity of the bacterial isolates. The Bauer-Kirby Disk Diffusion method was meticulously used to detect the antimicrobial susceptibility. Results: In the period from September 2016 to July 2017, specimens taken from 253 patients admitted to Pediatric intensive care units were sent for culture and sensitivity to pathology lab. Out of these specimens 61.9% showed no growth while 35.1% showed bacterial growth and 3 % showed fungal growth. Of the specimen that showed bacterial growth, Ceftriaxone was tested against Klebsiella, Acinetobacter, Pseudomonas, E.Coli, Staphylococcus Aureus and Salmonella. In this study the overall resistance for Ceftriaxone was 92.3%. In the data collected, Ceftriaxone showed 93.1% resistance in Holy Family Hospital and 96.4% in Benazir Bhutto Hospital. Conclusion: In light of previous relevant studies, our study shows further decline in effectiveness Ceftriaxone when used in treatment against bacterial infection in pediatric intensive care units.